Predictors of clinical outcomes in endodontic microsurgery: a systematic review and meta-analysis - Claudia García-Guerrero; Sara Quijano Guauque; Nicolás Molano; Gerardo Antonio Pineda; Javier L. Nino-Barrera; Dairo Javier Marín-Zuluaga (Ariesdue, 2017)
The prevalence of recurrent periapical lesions has been reported between 43 and 65%, endodontic microsurgery (EM) is an alternative treatment option of recurrent periapical lesions. Aim: the aim of the present study was to systematically quantify the effects of the association "clinical factors/follow-up period" on EM outcomes. Methodology: Two researchers conducted a literature search from 2005 to 2015. Searched databases were MEDLINE, Evidence-based Endodontics, Cochrane Library, EMBASE, LILACS, SCIELO, Trip-Database. Tables of contents of endodontic journals and references listed on retrieved articles were searched as well. A residual heterogeneity test set at 95% confidence interval controlled sample variability of each study. Meta-regression estimated the factor/follow-up period on the outcomes of the ME. Results: 1242 articles were identified, 10 of which were included for meta-regression. On average, EM was 84.13% successful when evaluated from 1 to 6 years. The heterogeneity analysis (P = 0.87) established the total variability of 8% in reference to sample variability. It was determined that a loss of "Crestal Bone Height" >3 mm proportionally predicts, from the second year on, an increased risk of EM failure (OR = 1.33, 90%CI, 1.01-1.77; P = 0.09). Factors such as "retro-filling material" (P = 0.0002), "presurgical clinical signs" (P = 0.0116), and "dentinal root defects" (P = 0.0001) are considered significant risk factors for EM failure without association to time. Conclusions: EM could be considered clinically successful over time. The factor "crestal bone height" estimated a predictive and progressive association of healing from the second year on. Different root-end filling materials aside from MTA could be associated with EM failure, without association with follow-up periods. *Registration Code: CRD42015029593, PROSPERO database.